Kualitas Ikan Kembung (Rastrelliger kanagurta) Setelah Perendaman Dalam Kitosan ditinjau dari Aspek Mikrobiologi dan Organoleptik - Ari Hepi Yanti, Gustini, Siti Khotimah (Universitas Tanjungpura, 2014)
The efforts that should be made to maintain the quality of fish is by using antimicrobial compounds, one of which is chitosan. The use of chitosan in this study was to determine the effect and optimum concentration of chitosan in maintaining the quality of mackerel (Rastrelliger kanagurta) from the microbiological and organoleptic aspects. The study used a Completely Randomized Design (RAL) with 3 variations of chitosan concentration is 1%, 2% and 3% dissolved in 1% acetic acid. The control used was acetate 1% solution and distilled weter. Observations were made after the fish are kept for 24 hours with the observation parameters of Total Plate Count (TPC), organoleptic and the fish pH. Based on the Analysis of Variance (ANOVA), the result showed that the administration of chitosan on mackerel did not significantly affect the value of TPC and organoleptic, but the increase in the total number of bacteria in mackerel was lower than without the provision of chitosan. Chitosan was also able to reduce the value of mackerel organoleptic lower than without the provision of chitosan. Mackerel stored for 24 hours at each treatment increased the pH 5 to 7, which shows that the fish has undergone a process of decomposition.